The Challenge of Stability Niklas Luhmann's Early Political Sociology and Constitutional Adjudication in the United States and Germany - Shulman, Theodor (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2023)
Niklas Luhmann's early systems-theoretical conception of functional differentiation holds both normative and empirical insights for our understanding of constitutional adjudication. For example, Luhmann's conception of legal autonomy may help to shed new light on the countermajoritarian difficulty. Secondly, his theory of how the political system is differentiated into two sub-systems can improve our conceptual understanding of judicial politicization. To illustrate this potential, this book applies "Legitimation durch Verfahren" in particular and Luhmann's early systems theory in general to Germany's Federal Constitutional Court and the United States Supreme Court.